Deformačně napěťová analýza vybraného hasícího přístroje - Češek, Jakub (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2017)
Bakalářská práce se zabývá deformačně napěťovou analýzou vybraného hasicího přístroje. V této práci je zkoumáno to, jaký vliv má dno tlakové nádoby na napětí a deformaci. Deformačně napěťová analýza je řešená na úrovni membránové a momentové teorie skořepin. Výsledné hodnoty těchto teorií jsou porovnány pomocí metody konečných prvků (MKP) v systému Ansys. V závěru práce je vše náležitě zhodnoceno.

Bachelor’s thesis deals with stress-strain analysis of chosen extinguisher. Within this thesis, different types of closures are summarized and their influence in stress state is thoroughly analyzed. The stress-strain analysis is solved by using momentum shell theory as well as membrane shell theory. At the end of this thesis numerical solutions by using Finite Elements Method (FEM) is performed in Ansys software. All results are compared in conclusion of the thesis.
Stress-strain analysis of a chosen fire extinguisher
Keywords: tlaková nádoba; skořepina; deformačně napěťová analýza; osová symetrie; Ansys; pressure vessel; shell; stress strain analysis; axisymmetric problem; Ansys